Penanaman Sikap Kewarganegaraan melalui Pembelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) Peserta Didik di Madrasah Ibtidaiyah Negeri 6 Pesisir Selatan Sumatera Barat - Rendy Nugraha Frasandy; Risa Bellawati; Remiswal Remiswal; Feni Risal ‘Alala (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This research is based on the anxiety of educators who observe the majority of students who have not applied citizenship attitudes such as honesty and responsibility both in the classroom and in the madrasa environment. Yet through learning PPKn (Pendidikan Pancasila dan Kewarganegaraan) in the classroom, educators have taught, instilled and even modeled directly on students. The purpose of the study was to describe the inculcation of citizenship attitudes such as honest attitude and attitude of responsibility through learning PPKn. This type of research is field research with qualitative descriptive methods. The data source of this study consisted of primary data sources namely educators and class III students and secondary data sources namely the headmaster of madrasah, other educational staff at Madrasah Ibtidaiyah Negeri 6 Pesisir Selatan. Data collection techniques using interviews, observation and documentation. The data that has been collected is then analyzed by means of data reduction, data presentation and drawing conclusions. Testing the credibility of the data researchers do by triangulating sources and methods. The results showed that the inculcation of the value of citizenship by educators was carried out in the following manner; First, in instilling honest attitudes educators convey directly and repeatedly in class, giving examples of being honest with students, paying attention to students' honesty and giving advice to students if they are not being honest. Second, in instilling the attitude of responsibility educators convey directly and repeatedly, giving examples of being responsible, paying attention to the attitude of responsibility of students and advising the importance of students being responsible in their activities.